INFLUENCE OF EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CULTURE TOWARDS EMPLOYEE PERFORMANCE - Juliorita Alfachtur Nafi' Hutama; Ella Jauvani Sagala (Manajemen Bisnis, 2019)
Human resources (HR) have a very important role in an organization.Of course, by processing good human resources can drive the performance of an organization. This research was conducted at PT. XYZ, a company in the telecommunications sector in Indonesia. The purpose of this study is to determine the application of employee engagement, organizational culture conditions and performance at the company. The method used in this study is a quantitative method. This research is descriptive and causal research. The population in this study were employees of the PT. XYZ. Data analysis in this study used descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, and multiple regression analysis. The findings in this study concluded that employee engagement and organizational culture had a positive and significant influence partially on performance. In addition, it can be concluded that employee engagement and organizational culture have a significant simultaneous influence on performance.